Pre-service Teachers’ Perceptions of the New Pedagogical Deep Learning (NPDL) - yeni setyowati; Ayu Rahayu; Prasetyo Listiaji (Journal of Environmental and Science Education, 2025)
This study aimed to investigate the perceptions of pre-service Science Education teachers regarding New Pedagogical Deep Learning (NPDL) in Indonesia. Employing a descriptive survey design, the research was conducted in Central Java Province and involved a sample of 88 pre-service Science Education teachers. Data collection was performed using a questionnaire consisting of 10 items, distributed through Google Forms, complemented by follow-up interviews. Quantitative data analysis with a descriptive approach was utilized to analyze the collected data. The study yielded three primary findings. First, Science Education pre-service teachers possess a basic understanding of the Deep Learning concept, although 16% of them exhibit misconceptions by equating Deep Learning solely with artificial intelligence (AI). Second, these pre-service teachers demonstrate interest in implementing Deep Learning in the classroom; however, they require further training to deepen their understanding of what Deep Learning entails and how to effectively apply it in science education at the school level. Third, pre-service teachers are ready to implement Deep Learning and require strong ecosystem support. They express a keen interest in applying Deep Learning in the classroom.